We need to verify that sinx/(1-xosx)= (1+cosx)/sinx

We know that sin^2(x) + cos^2(x)=1

==> sin^2(x)= 1-cos^2(x)

==> sin^2(x)= (1-cos(x))(1+cos(x))

==> (sinx)(sinx)= (1-cosx)(1+cosx)

Now divide by (sinx)(1-cosx)

==> sinx/(1-cosx)=(1+cosx)/sinx)

We need to verify that sinx/(1-xosx)= (1+cosx)/sinx

We know that sin^2(x) + cos^2(x)=1

==> sin^2(x)= 1-cos^2(x)

==> sin^2(x)= (1-cos(x))(1+cos(x))

==> (sinx)(sinx)= (1-cosx)(1+cosx)

Now divide by (sinx)(1-cosx)

==> sinx/(1-cosx)=(1+cosx)/sinx)